Assessment of suspected vascular rings and slings and/or airway pathologies using magnetic resonance imaging rather than computed tomography - Sommerburg, Olaf; Helling-Bakki, Astrid; Alrajab, Abdulsattar; Schenk, Jens-Peter; Springer, Wolfgang; Mall, Marcus A.; Loukanov, Tsvetomir; Eichhorn, Joachim (Respiration, 2019)
Background: Congenital cardiovascular malformations (CCVM) may cause infrequently airway pathologies (AP) in children and are of prognostic and therapeutic relevance. While computed tomography (CT) is considered first-line imaging modality in many centres, we started using magnetic resonance imaging (MRI) more and more in the last years to detect CCVM and AP to avoid radiation in this patient group. Objective: The aim of this retrospective study was to determine and to compare the diagnostic accuracy of CT and MRI when used to detect CCVM and/or AP. Methods: All patients suspected to have CCVM and/or AP and examined either by CT or MRI between 2000 and 2013 in our hospital were included. Extension and type of CCVM, as well as their relationship to esophagus, trachea or bronchi were assessed and related to findings of tracheobronchoscopy, cardiac catheterization or surgery if available. Results: One hundred six patients (median [range] 4 years [2 days to 66 years]) were examined by CT (n = 27) or MRI (n = 79). In 78 patients (74%), CCVM and/or AP were found with either of the imaging methods. CCVM were found in 63 subjects. Forty-six of 63 subjects had both, CCVM and AP. The presence of CCVM was always detected correctly by CT or MRI, although both techniques had a weakness detecting atretic segments directly. AP (n = 61) were correctly diagnosed in all patients not intubated for artificial ventilation by CT (n = 17) and in all but 2 patients by MRI (39 out of 41). Conclusions: MRI is sensitive to detect CCVM associated with AP equally to CT without any radiation exposure.
Gesehen am 27.06.2019
Der Name des ersten Autors ist auf der Frontdoor der Zeitschrift fälschlich als O. Sommburg angegeben